Media Literacy, Consumer Trust, Product Prices, Distribution, and Purchasing Decisions in Online Business: A Study of Students at Satya Wiyata Mandala University - Dian Anugrah Sanusi; Aris Widodo; Letarius Tunjanan (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2023)
This study aims to determine the effect of media literacy, consumer trust, product prices, distribution on purchasing decisions through online business. This study uses a quantitative research approach. The population of this study were all students in the city of Makassar who had purchased products online and the total sample was 91 respondents, taken by probability sampling. Data collection techniques in the form of distributing questionnaires through google form. The data analysis technique used is statistical analysis using SPSS. The results of the study show that media literacy, consumer trust, product prices, product distribution have a significant influence on purchasing decisions in online businesses. This research contributes to the development of economics, especially in the field of online business and online business people to see the prospects of online-based marketing activities, as a consideration in determining the next marketing strategy given the growing development of online-based marketingusion